Behçet's Disease and Pregnancy. Issue 9 (26th August 2013) - Noel, Nicolas; Wechsler, Bertrand; Nizard, Jacky; Costedoat‐Chalumeau, Nathalie; Boutin, Du Le Thi Huong; Dommergues, Marc; Vauthier‐Brouzes, Danièle; Cacoub, Patrice; Saadoun, David
<x xml:space="preserve">Abstract</x> Objective To describe the interplay between Behçet's disease (BD) and pregnancy. Methods This retrospective study included 76 pregnancies in 46 patients fulfilling the international criteria for BD. The median age of the patients at the time of entry into the study was 28.4 years (interquartile range 22.8–30.9 years). Patients were used as their own historical controls to assess the incidence of BD flares during pregnancy and before or after pregnancy. Factors associated with the occurrence of complications during pregnancy were assessed. Results Among the 76 pregnancies with BD analyzed, 27 (35.5%) were associated with worsening of the symptoms of BD flare; oral and genital ulcerations (78.4% and 67.6%, respectively) as well as ocular complications (32.4%) were the most frequent. The mean ± SD annual rates of BD flares were 0.49 ± 0.72 during pregnancy and 1.46 ± 2.42 during the nonobstetric period (P = 0.018). The proportion of BD flares tended to be lower in patients treated with colchicine (27.9% versus 45.4% of patients not treated with colchicine; P = 0.11). The overall rate of complications during pregnancy was 15.8%. The complications included miscarriage (5 patients), cesarean delivery (3 patients), medical termination of pregnancy (2 patients), hemolysis, elevated liver enzymes, and low platelets syndrome (1 patient), and immune thrombocytopenia (1 patient). There was a statistically significant association between a history of deep vein thrombosis in BD and the risk of obstetric complications (odds ratio 7.25, 95% confidence interval 1.21–43.46, P = 0.029). Neither gestational age at delivery nor neonatal outcome was influenced by BD. Conclusion The disease course in BD seems to improve during pregnancy, mostly in patients who are treated with colchicine. Pregnancy in patients with BD appears not to be associated with an increased rate of pregnancy‐related complications.